Comparison of Applications to Evaluate Groundwater Recharge at Lower Kelantan River Basin, Malaysia - Nur Hayati, Hussin; Ismail, Yusoff; Raksmey, May (MDPI AG, 2020)
Groundwater has supported 70% of the water supply at the Lower Kelantan River Basin (LKRB) since the 1930s and demand for groundwater increases annually. Groundwater has been abstracted from shallow and deep aquifers. However, a comprehensive study on groundwater recharge estimation has never been reported. This study evaluated various methods to quantify recharge rate using chloride mass balance (CMB), water table fluctuation (WTF), temperature–depth profiles (TDP), and groundwater modelling coupled with water balance (GM(WB)). Recharge estimation using CMB, WTF, TDP, and GM(WB) showed high variability within 8% to 68% of annual rainfall. CMB is range from 16% to 68%, WTF 11% to 19%, TDP 8% to 11%, and GM(WB) 7% to 12% of annual rainfall, respectively. At 11%, recharge from GM(WB) was the best method for estimation because the model was constructed and calibrated using locally derived input parameters. GM(WB) is the only method involved with calibration and validation process to reduce the uncertainty. The WTF method based on long-term hydrological records gives a reasonable recharge value, in good agreement with GM(WB) and these methods can be paired to ensure the reliability of recharge value approximation in the same ranges. Applying various methods has given insight into methods selection to quantify recharge at LKRB and it is recommended that a lysimeter is installed as a direct method to estimate recharge.